Correlation of IDH1 gene expression error in breast tumor biopsy in patients with invasive ductal carcinoma: IDH1 gene expression in breast cancer - Rostami, Behzad; Kahrizi, Sepehr; Ghorbani Yekta, Batool; Ghadyani, Rezvaneh; Keramatinia, Aliasghar; Hoseini, Seyed Jalil; Karima, Saeed; Nikzamir, Abdol Rahim; Mansouri, Neda; Chen, Muzi; Movafagh, Abolfazl (Cellular and Molecular Biology, 2024)
One of the most important cancers in terms of worldwide prevalence is breast tumors, which have been less investigated in correlation with the enzyme Isocitrate Dehydrogenase 1 (IDH1) gene. The aim of this study was that expression of this gene could have significant effects on the progression of metastasis and invasive disease in breast cancer patients. We used the molecular method of RT-PCR with SYBR-Green to analyze breast tumor tissue from patients with metastasis and non-metastasis, the latter confirmed by the pathology department of Shohada-e Tajrish Hospital (serving as a control group). Also, patients population and its relationship with the degree of tumor in the IDH1 gene was investigated. The IDH1 gene has shown high expression in patients with metastatic breast cancer rather than in patients with non-metastatic breast cancer. The metastatic samples were compared with non-metastatic samples for IDH1 mRNA expression. In this research work, 72.5% (29 samples) were up-regulated in comparison to 27.5% of samples (11 samples) that did not exhibit high expression (P=0.000). This study examined the IDH1 gene expression, suggesting that changes in this gene's expression could impact the prognosis of breast cancer. However, further research is needed to draw definitive conclusions.